Neuroeconomics: Tax Planning and the Role of Digital Literacy as a Moderation - Tio Arriela Doloksaribu; Novita Rifaul Kirom; Rachma Yuliana; Dwi Ekasari Harmadji (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Taxpayer awareness in fulfilling their tax needs is closely related to individual logical awareness. Corporate taxpayer awareness is closely related to tax planning in order to save business. This study aims to determine the psychological and logical realm of tax planning. The research method used is quantitative and through incidental techniques, 100 respondents were obtained. The results of the study indicate that Tax Literacy has an effect on Tax Planning, as well as Taxpayer Morale has an effect on Taxpayer Planning. Furthermore, digital literacy has been shown to moderate the relationship between tax literacy and tax planning, but does not act as a moderator in the influence of tax morale on tax planning. Based on the results of this study, tax planning can be improved by considering the role of individual psychological and logical aspects from a neuroeconomic perspective. The rational and logical aspects of individual tax planners can be the basis for triggering reasonable tax planning and not violating applicable regulations.